Impact of lifelong e-learning : Evidence and guidance - Andresen, Bent B. (2006)
This paper deals with lifelong learning. Based on a three-year case study it provides evidence of innovations in this area. The paper aims to add to the body of work in blended learning by providing evidence of knowledge, persuasion, decision, implementation, and confirmation of learning innovations. In particular, the paper provides guidance for future development